Czego mogą się nauczyć od Władysława Witwickiego współcześnie psychologowie? - Bobryk, Jerzy (Filozofia Nauki, 1999)
The article is devoted to the evaluation of the ecological alternative in cognitive psychology. The theory of „extended minds” is discussed in this paper as a version of ecological psychology. The authors of the theory of extended mind advocate „active externalism”, based on the active role of the environment in driving cognitive processes. The environment, driving cognitive processes, comprises books, diagrams, language, and other culture products. Władysław Witwicki's psychology and his idea of real presence of persons in cultural products which they create, provide a conceptual framework for the undertaken analysis and evaluation.